EVALUATION OF NITRIFICATION PROCESS IN CONSTRUCTED WETLANDS: A REVIEW ON NOVEL BIOLOGICAL NITROGEN REMOVAL PROCESSES - Yasir Talib Hameed; Narmeen Abdalwahhab Abdalqadir; Hala Husham Nussrat; Khaled muftah Shahot (Journal of Engineering and Sustainable Development, 2022)
Constructed wetlands attracted the attention of researchers as a sustainable, economic, and efficient wastewater treatment technique. Many papers showed the efficient performance of constructed wetlands to treat municipal, industrial, livestock, petroleum, and other types of wastewater, effectively removing organic matters, phosphate, nitrogen, and contaminants of emerging concern such as pharmaceuticals and antibiotics. There have been numerous reviews in the literature that studied nitrogen removal in constructed wetlands from different perspectives. However, the majority are concerned about the conventional nitrification process. It is worth mentioning that some biological nitrogen pathways other than the conventional nitrification process were implemented in constructed wetlands efficiently such as partial nitrification and denitrification, simultaneous nitrification and denitrification, anaerobic ammonium oxidation, and completely autotrophic nitrogen removal over nitrite which have been reviewed in this study. The outcomes of this study showed that anaerobic ammonium oxidation is the most common pathway applied in constructed wetlands. Moreover, this review showed that the efficient performance of these novel pathways is constrained by the difficulty of controlling the operating parameters such as dissolved oxygen, temperature, and pH.